2023
DOI: 10.1021/acs.energyfuels.3c01420
|View full text |Cite
|
Sign up to set email alerts
|

Highly Flexible All-Solid-State Supercapacitors Based on MXene/CNT Composites

Abstract: MXene, a promising electrode material for supercapacitors, has excellent mechanical properties, hydrophilicity, metallic conductivity, and rich surface chemistry. However, the self-restacking of MXene nanosheets due to the strong van der Waals force makes it difficult to assemble them into electrodes. Here, continuous, ultrathin carbon nanotube (CNT) films are introduced as interlayers between MXene layers to prevent self-restacking during the assembly process, and freeze-drying is used to obtain composite fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…238 These excellent properties have aroused wide concern in related fields, such as ion batteries, electrocatalysis, supercapacitors, and hydrogen storage. 239 Xu et al 240 showed excellent electrochemical properties, and the capacitance retention of 99% over 5000 cycles. The combination of precious metals, transition metal compounds, and nonmetals with MXenes is critical to enhance the active sites and stability to improve hydrogen storage performance.…”
Section: Carbonaceous Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…238 These excellent properties have aroused wide concern in related fields, such as ion batteries, electrocatalysis, supercapacitors, and hydrogen storage. 239 Xu et al 240 showed excellent electrochemical properties, and the capacitance retention of 99% over 5000 cycles. The combination of precious metals, transition metal compounds, and nonmetals with MXenes is critical to enhance the active sites and stability to improve hydrogen storage performance.…”
Section: Carbonaceous Materialsmentioning
confidence: 99%
“…These excellent properties have aroused wide concern in related fields, such as ion batteries, electrocatalysis, supercapacitors, and hydrogen storage . Xu et al utilized continuous ultrathin carbon nanotube films as an interlayer between MXenes layers to prevent self-overlapping during assembly. It was found that the MXenes/CNT composite films showed excellent electrochemical properties, and the capacitance retention of 99% over 5000 cycles.…”
Section: Electrochemical Hydrogen Storage Materialsmentioning
confidence: 99%
“…prepared continuous, ultrathin CNTs through chemical vapor deposition (CVD), and prepared MXene/CNT composite films by immersing CNTs into modified MXene suspensions using a roll immersion method. The composite films with layered porous structure were obtained by freeze‐drying, with a capacitance of 550 F g −1 for 80 wt%‐MXene/CNT film at 2 mV s −1 [90] . Wang et al.…”
Section: Freestanding Flexible Mxene Composites For Supercapacitorsmentioning
confidence: 99%
“…The composite films with layered porous structure were obtained by freezedrying, with a capacitance of 550 F g À 1 for 80 wt%-MXene/CNT film at 2 mV s À 1 . [90] Wang et al prepared V 2 CT x MXene (VCT-K) co-modified with K + and À O functional groups for Li + ions storage, in which K + ions increase the interlayer space and the surface modification of the À O groups improves the reversible capacity of the Li + ions storage. And further combined it with single-walled carbon nanotubes (SWCNT) to obtain a freestanding V 2 CT x composite film with a 3D conductive network (VCT-K@C).…”
Section: Mxene/carbon-based Binary Composite Filmsmentioning
confidence: 99%
“…They have a large surface area, a variable pore size distribution, and good electrical conductivity. , Several carbon-based materials have been investigated as electrode materials, including graphene, carbon nanotubes (CNTs), carbon nanofibers (CNFs), graphitic carbon nitride (g-C 3 N), biochar and activated carbon. Thus, due to their excellent bending strength and mechanical stability, graphene and CNTs are the best electrode materials for stretchable and flexible supercapacitors (FSCs) . As a result, significant progress has been made in studying carbon NMs for creating innovative electrode materials in various SCs for suitable energy storage.…”
Section: Introductionmentioning
confidence: 99%